2010
DOI: 10.5038/1827-806x.39.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and opportunistic microorganisms in caves

Abstract: With today's leisure tourism, the frequency of visits to many caves makes it necessary to know about possible potentially pathogenic microorganisms in caves, determine their reservoirs, and inform the public about the consequences of such visits. Our data reveal that caves could be a potential danger to visitors because of the presence of opportunistic microorganisms, whose existence and possible development in humans is currently unknown. Caves, bacteria, fungi, virus, opportunistic pathogens Received 26 Ok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 77 publications
2
64
1
Order By: Relevance
“…We contend that the bacteria reported are not indigenous to the cave but carried into it by humans because, first, humans leave man-made litter in the cave along with feces, urine, menstrual blood, and semen; second, the bacteria found in other caves, including some with recreational uses but with better visiting strategies and cave protection, do not resemble the bacteria we report in that the ones present in Las Escaleras are almost all pathogenic for humans; third, bacteria isolated from caves as their indigenous habitats and considered pathogenic mostly belong to the Actinobacteria (particularly those of the genera Nocardia, Mycobacterium, Gordonia, Rhodococcus, and Streptomyces; Jurado et al, 2010), while others are members of the Alphaproteobacteria groups such as Inquilinus limosus or Aurantimonas spp., members of the genus Afipia, or Staphylococcus aureus, none of them found in this work; and finally, although not completely conclusive, of forty-two species of bacteria in a catalog of bacteria (González-Quiñones et al, 2014) found on the skin of Sturnira lilium and S. bogotensis bats (Chiroptera: Phyllostomidae), only two (E. coli and C. freundii) were also present in this cave.…”
Section: Discussioncontrasting
confidence: 58%
“…We contend that the bacteria reported are not indigenous to the cave but carried into it by humans because, first, humans leave man-made litter in the cave along with feces, urine, menstrual blood, and semen; second, the bacteria found in other caves, including some with recreational uses but with better visiting strategies and cave protection, do not resemble the bacteria we report in that the ones present in Las Escaleras are almost all pathogenic for humans; third, bacteria isolated from caves as their indigenous habitats and considered pathogenic mostly belong to the Actinobacteria (particularly those of the genera Nocardia, Mycobacterium, Gordonia, Rhodococcus, and Streptomyces; Jurado et al, 2010), while others are members of the Alphaproteobacteria groups such as Inquilinus limosus or Aurantimonas spp., members of the genus Afipia, or Staphylococcus aureus, none of them found in this work; and finally, although not completely conclusive, of forty-two species of bacteria in a catalog of bacteria (González-Quiñones et al, 2014) found on the skin of Sturnira lilium and S. bogotensis bats (Chiroptera: Phyllostomidae), only two (E. coli and C. freundii) were also present in this cave.…”
Section: Discussioncontrasting
confidence: 58%
“…The highest detection rate of mycobacterial DNA shown in Table 1 could be caused by the detection of dead or living but not in vitro culturable environmental mycobacteria. Data on the detection of mycobacteria in caves is quite limited (Breitbart et al 2009;Jurado et al 2010;De Mandal et al 2015a;De Mandal et al 2015b). However, there are previously published studies describing the massive occurrence of different species of moulds in Moravian and Slovak karstic caves (Lukesova and Novakova 2009;Novakova 2009;Hubka et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, a monograph describing the ecology of mycobacteria, which analysed the occurrence of mycobacteria in the environment and which was based on more than 6500 literary sources from databases including PubMed, Web of Science and others, did not mention any detection of mycobacteria in karstic environments (Kazda et al 2009). Recent results showing the presence of mycobacteria in cave environments are also limited (Breitbart et al 2009;Jurado et al 2010;De Mandal et al 2015a;De Mandal et al 2015b). Due to the ubiquitous occurrence of mycobacteria in the environment it is supposed that they are transported to the cave system from the relevant water catchment area and that they are able to survive there in different matrices.…”
mentioning
confidence: 99%
“…Organic matter contamination and fungal widespread are relatively common in caves open for tourist visits (Jurado et al, 2010b;Martin-Sanchez et al, 2012a,b), these findings indicate an alarming scenario as a small amount of organic matter could generate a fungal bloom despite the lack of other factors associated with these caves (Mulec and Kosi, 2009;Jurado et al, 2010b;Porca et al, 2011;Martin-Sanchez et al, 2012b;Šebela et al, 2013;Mulec, 2014). Several species of fungi are human pathogens and could be transported by visitors and proliferate in the closed environment of these caves (Jurado et al, 2010a;Taylor et al, 2013), which could be a major health risk to anyone who enters the cave.…”
Section: Discussionmentioning
confidence: 99%